If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4x + 8 = 85 Reorder the terms: 8 + 3x + 4x = 85 Combine like terms: 3x + 4x = 7x 8 + 7x = 85 Solving 8 + 7x = 85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 7x = 85 + -8 Combine like terms: 8 + -8 = 0 0 + 7x = 85 + -8 7x = 85 + -8 Combine like terms: 85 + -8 = 77 7x = 77 Divide each side by '7'. x = 11 Simplifying x = 11
| 5x(5x)+5=250 | | x/6-11=2 | | 58=19-3x | | 3=-5k | | -n+5n-18=-10 | | 12x-15=21 | | -8x+4(7+8x)=4x+7 | | x/8-7=12 | | 5(4-5x)+5=-5(x+7) | | -12n+39=-4h-17 | | 8t(t-5)=0 | | 3(4y-1)=-16y | | 4a(6-7b)=2c | | 30n-6=3 | | x/15+8=23 | | 4.5=.5(x-7.1) | | -8+4(7+8x)=4x+7 | | 4=17-m | | .3=.5f-.7 | | x/16+14=19 | | X^2+22=6x | | 2mx^2-3x-mx+2=0 | | D-16=-15 | | 2t-5= | | 1.5-0.02x=-1.14 | | x/2+4=18 | | -13m+11m=10 | | 0.02(y-8)+0.04y=0.14y-0.6 | | 2mx^2+3x-mx+2=0 | | f(6)=x^2-10x+1 | | 12x-1184=7x-1976 | | x/12-3=3 |